The Effectiveness of Group Logotherapy on Transcendental Future Orientation and Interpersonal Forgiveness in Individuals with Existential Anxiety - Hoseinifar, Roya; Anasseri, Mehryar (Mental Health and Lifestyle Journal, 2026)
The present study aimed to determine the effectiveness of group logotherapy on transcendental future orientation and interpersonal forgiveness in individuals with existential anxiety. This study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of all individuals with existential anxiety who referred to Avid Counseling and Psychology Center in Tehran in 2025. In this study, 24 individuals were selected from the population using a non-random purposive (goal-based) sampling method based on inclusion criteria. Participants were then randomly assigned to an experimental group (n = 12) and a control group (n = 12). Following attrition, 10 participants successfully completed the intervention. The Transcendental Future Time Perspective Questionnaire (Boyd & Zimbardo, 1997), the Interpersonal Forgiveness Questionnaire (Ehteshamzadeh et al., 2011), and the Existential Anxiety Questionnaire (Good, 1974) were used in this study. The experimental group participated in 12 sessions of group logotherapy, each lasting 90 minutes, while the control group received no intervention. The collected data were analyzed using multivariate and univariate analysis of covariance. The results indicated a statistically significant difference between the posttest mean scores of the experimental and control groups (p < .01). The findings suggest that group logotherapy can be used as an effective therapeutic approach to enhance transcendental future orientation and interpersonal forgiveness in individuals with existential anxiety.